IMPLEMENTASI PEMBELAJARAN IPS BERBASIS KEARIFAN LOKAL UNTUK MENANAMKAN NILAI-NILAI BUDAYA BIMA SEJAK DINI PADA SEKOLAH DASAR - Trimansyah, Trimansyah (Prodi PGMI STIT Sunan Giri Bima, 2025)
This study aims to examine the implementation of Social Science (IPS) learning based on local wisdom in instilling Bima cultural values from an early age in elementary school students. Social Science learning based on local wisdom is expected to help students understand and appreciate the culture and traditions of the Bima community. This study employs a descriptive qualitative approach with data collection techniques that include discussion, observation, simulation, and interviews with local communities to explore cultural values such as mutual cooperation, honesty, and social responsibility embedded in Bima culture, such as agriculture, trade, economy, and traditional Bima crafts. The data analysis technique involves data collection, data reduction, data display, and conclusion drawing. The results of the study indicate that the implementation of Social Science learning based on local wisdom can enhance students' understanding of applying Bima cultural values. It also strengthens their awareness of the importance of preserving regional culture. Furthermore, students show improvements in attitudes and behaviors that reflect Bima cultural values, such as honesty, discipline, mutual cooperation, responsibility embodying the meaning of the Bima cultural principle